Sea of the caliphs : the Mediterranean in the medieval Islamic world - Picard, Christophe (The Belknap Press of Harvard University Press, 2018)
Christophe Picard recounts the adventures of Muslim sailors who competed with Greek and Latin seamen for control of the 7th-century Mediterranean. By the time Christian powers took over trade routes in the 13th century, a Muslim identity that operated within, and in opposition to, Europe had been shaped by encounters across the sea of the caliphs.